Perancangan Desain Bangunan Pengendalian Abrasi Pantai Di Daerah Muara Sungai Muarabangkahulu - Medianto Mulyadi; Meilani Belladona (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2017)
Zakat beach is one of the water tourism places frequented by tourists, but along the way there are several points that have abrasion due to erosion of waves, wind and tidal sea water. This research aims to make the design of coastal protective structures so that the abrasion can be overcome. The data used is wind data. Primary data is a measurement of water level on the estuary of the river Bangkahulu with the help of coal farmers around the location of the review. The design of the abrasion retaining building uses a sloping sidewall with an arrangement of rocks arranged in such a way. Significant wave heights are sought using wave forecasting with an HS value of 1.054 meters and a significant wave period of 5.31 seconds. The calculation result is used to calculate wave height due to sea floor depth change, Ks value is 1,092, refractive coefficient value = 0,736 and wave height at depth 1,52 is 0,847 m. The height and depth of the breaking wave are Hb = 1.005 meters and db = 0.985 meters. Elevation of the breakwater peak with a high free of 0.234 m without a tsunami is 4.212 meters. The peak width of the breakwater building is 0.61 meters with the weight and thick of the main protective layer of 103 Kg and 0.4 meters and the number of granules per 10 meters is 25 grains.